Mortalité et aléas hydro-climatiques dans les outre-mers français depuis 1950 (Guadeloupe, Martinique, Nouvelle-Calédonie) - Frédéric Leone; Anaïs Coulon; Eliott Libner; Noémie Nérin; Samuel Battut; Victoria Bigot; Thomas Candela; Stéphanie Defossez (Espace populations sociétés)
This article analyzes the locations, causes, circumstances of death and profiles of victims induced by hydro-climatic hazards, including cyclones, in Guadeloupe (101 deaths), Martinique (102) and New Caledonia (59) since 1950. It is based on a new geo-historical database developed from archives and field surveys. It makes it possible to make comparisons, to show developments, to highlight territorial specificities and clearly evolving risk behaviors. Many lessons have emerged to guide risk prevention in the three territories, particularly during hurricane seasons, but not only that.